Patients with Long COVID continue to experience significant symptoms at 12 months and factors associated with improvement: A prospective cohort study in France (PERSICOR) - Dominique Salmon; Dorsaf Slama; Françoise Linard; Nicolas Dumesges; Valérie Le Baut; Florence Hakim; Pauline Oustric; Emilie Seyrat; Patricia Thoreux; Esaie Marshall (International Journal of Infectious Diseases, 2024)
Objectives: This study examines long COVID symptoms course over 12 months, their impact on daily life, and associated factors for symptom relief. Methods: A prospective cohort study included 231 participants with long COVID at 12-month follow-up. Data on characteristics, symptom course, and remission were collected using a questionnaire and a remission scale. Poisson regression models were used to estimate the prevalence rate ratio (PRR) and 95% confidence intervals (CIs) for factors associated with symptom improvement. Results: Of the 231 participants, 63.2% developed SARS-CoV-2 antibodies before COVID-19 vaccination. At 12 months, only 8.7% (95% CI: 5.4-13.1%) reported complete remission, while 28.6% noted significant improvement. Most symptoms remained prevalent: asthenia (83.1%), neurocognitive/neurological (93.9%), cardiothoracic (77.9%), Musculoskeletal (78.8%). During long COVID, 62.2% stopped working, and only 32.5% resumed full-time professional activities. Presence of SARS-CoV-2 antibodies before vaccination increased the probability of improvement (aPRR: 1.60, P = 0.028), while ageusia at initial long COVID phase decreased the probability (aPRR: 0.38, P = 0.007). Conclusions: Long-COVID symptoms persisted in the majority of participants after 12 months, with significant impacts on daily life and work. SARS-CoV-2 antibodies were associated with better prognosis, while persistent ageusia indicated a lower probability of improvement. These findings highlight the need for ongoing support and care for individuals with long COVID.